On the nature of goethite, Mn-goethite and Co-goethite as supports for gold nanoparticles - Campo, Betiana Carla (2008)
Mn- and Co-substituted goethite (α-MnFeOOH and α-CoFeOOH) and pure goethite (α-FeOOH) were studied as supports for gold catalysts. The textural properties of these solids were studied by N2/77 K adsorption. Mn and Co substitutions gave rise to an increase of the specific surface area, as measured by BET equation. A DTA study indicated that the thermal stability of goethite was increased by Mn and Co incorporation. XRD analysis showed that both Mn and Co strongly modified goethite cell parameters, giving rise to an increase of the reducibility of both substituted oxyhydroxides, as measured by TPR. Three different samples were obtained by anchoring gold by direct anion exchange (DAE) method from HAuCl4: Au/α-FeOOH, Au/α-CoFeOOH and Au/α-MnFeOOH. FT-IR indicated that gold species were attached to OH goethite groups, while TEM analysis demonstrated that gold particles were in the nanometric range for all the samples. On pure goethite gold particles size distribution was relatively narrow, while for the cases of Au/α-MnFeOOH and Au/α-CoFeOOH a wide crystal size distribution were obtained. It is concluded that α-MnFeOOH and α-CoFeOOH are better supports for the gold particles since reducibility, thermal stability and specific surface area are higher than in the case of pure α-FeOOH. © 2007 Elsevier B.V. All rights reserved.